1981
DOI: 10.1115/1.3184473
|View full text |Cite
|
Sign up to set email alerts
|

Tooling Design for ECM—A Finite Element Approach

Abstract: Over the last few years several models have been suggested for analytical design of tools used in electrochemical machining of complex shaped workpieces. However, little success has been achieved in this direction. This is due to complex nature of interaction between the electrochemical machining parameters and lack of clear understanding of the mechanism of metal removal. This paper reports about the application of Finite Element Technique (FET) to design analysis of ECM tools. The results obtained have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…18 is based on the assumption that the current density J remains constant over an element of small length (dx) and for a small interval of time, ∆t. This equation yields values of y which agree well with the experimental data [11].…”
Section: (D) Interelectrode Gap (Ieg)supporting
confidence: 78%
See 1 more Smart Citation
“…18 is based on the assumption that the current density J remains constant over an element of small length (dx) and for a small interval of time, ∆t. This equation yields values of y which agree well with the experimental data [11].…”
Section: (D) Interelectrode Gap (Ieg)supporting
confidence: 78%
“…Different researchers [8][9][10][11][12] have also developed numerical methods for determining anode shape and/or tool design in ECM. Review of the literature has revealed that they have not analyzed the stray current attack and stagnation zones (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The inverse problem of electrochemical shaping with the aid of a shaped tool was considered in many works [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], which is connected with extensive practical use of this scheme and the importance of the perfection of calculation methods for designing costly tools of intricate shapes. The ECM of sculptured surfaces by an unshaped tool started to be developed only in the last few years, in particular, when performing electrochemical micromachining (ECMM).…”
Section: Theory Of Electrochemical Shapingmentioning
confidence: 99%
“…Step by step procedure followed for anode shape prediction is as follows [14]  Decide whether the analysis to be made is one, two or three dimensional.  Collect all the initial data in the proper units and, if necessary, preliminary computation (for example, flow velocity from the volumetric flow rate) is also done.…”
Section: Procedures For Anode Shape Predictionmentioning
confidence: 99%
“…Analytic approaches are used for tooling design such as the cosθ method [4,5], the complex variables method [6], and Semi-analytical and numerical techniques include the boundary elements method (BEM) [7][8][9][10], the finite difference method (FDM) [11][12][13], the finite volume method (FVM) and finite element method (FEM) [14,15]. The models used may greatly vary in terms of complexity.…”
Section: Introductionmentioning
confidence: 99%